RECORD OF SOME DEFORMED SPECIMENS OF CIRRHINUS MRIGALA (Ham-buch.) FROM RIVER TAWI IN JAMMU CITY - S. P. S. Dutta (The Bioscan, 2018)
Three adult truncated specimens of Cirrhinus mrigala were noticed among the fish collections made by fishermen from river Tawi, in Jammu city area, and have been described. Radiological analysis has revealed various types of vertebral column anomalies viz dome, trough, lordosis and kyphosis; irregular vertebral column, and ankylosis and kyphosis. These anomalous fishes have aberrant intestinal coiling and aberrations in air bladder lobes. Possible causes of deformities in the present case are most probably due to rising water pollution in river Tawi in the Jammu city and its downstream area.